A case of early gastric cancer with metastatic recurrence following curative endoscopic submucosal dissection - Yukihiro Morita; Hidenori Kimura; Osamu Inatomi; Akito Noguchi; Shuhei Shintani; Takayuki Imai; Masashi Ohno; Hiroshi Matsumoto; Atsushi Nishida; Sachiko Kaida; Masaji Tani; Ryoji Kushima; et al. (DEN Open)
Abstract A 70‐year‐old man was diagnosed with early gastric cancer with ulcerative findings. Endoscopic submucosal dissection as an absolute indication was performed, and en bloc resection was achieved. Pathological examination revealed a well‐differentiated adenocarcinoma, 3 × 2 mm in size, intramucosal, with an ulcerative scar, no lymphovascular invasion, and a tumor‐free margin. We diagnosed it as a curative resection and followed up with annual endoscopy. Sixteen months after endoscopic submucosal dissection, esophagogastroduodenoscopy revealed a singular ulcer scar; however, serum carcinoembryonic antigen level was elevated. Computed tomography scan showed wall thickening of the gastric antrum and an irregular mass on the dorsal side. Additionally, 18F‐fluorodeoxyglucose positron emission tomography/coomputed tomography showed 18F‐fluorodeoxyglucose uptake in the gastric antrum, irregular mass, and liver. Endoscopic ultrasonography revealed an internally heterogeneous mass in the gastric antrum region extending from the submucosal layer to the muscularis propria layer. Using an endoscopic ultrasonography‐guided fine needle biopsy with a 22‐gauge needle for the mass, we diagnosed local recurrence with the submucosal tumor‐like appearance, lymph node metastasis, and liver metastases. Unfortunately, the patient died of gastric cancer 3 months after the diagnosis. Here, we report a rare case of local recurrence in the submucosal layer, lymph node metastasis, and liver metastases 16 months after curative endoscopic submucosal dissection.